Penggunaan Media Wayang Daun dalam Mengembangkan Interaksi Siswa Terhadap Lingkungan Belajar Di SD Negeri 10 Pangkalapinang - Sasih K Arafatun; Sri Sugiyarti (Universitas Muhammadiyah Bangka Belitung, 2019)
Education can be obtained anywhere. The surrounding environment is a concrete education that makes it easy for students to get to know and learn it. This study aims to study the fourth grade students of SD 10 Pangkalpinang on learning environments. The method used in this research is descriptive qualitative. This research was conducted at SD Negeri 10 Even Pangkalpinangsester, in May 2018, academic year 2017/2018 and used data collection techniques namely observation and interviews and data analysis namely data reduction, data presentation and conclusion or verification. Research results obtained: a. Social environment, in the classroom, the social environment that is closest to students is the teacher and other students. The social interaction is intertwined from methods such as examples not examples ie the teacher divides students into 3 groups namely production groups, distribution groups and consumption groups, b. Natural environment, media making materials utilize nature, such as dried leaves that are converted into shadow puppets, c. The artificial environment consists of a school garden which is provided with regularly planted trees and flowering plants.